Optimization of Deacetylation Process for Regenerated Cellulose Hollow Fiber Membranes - Xuezhong He (International Journal of Polymer Science)
Cellulose acetate (CA) hollow fibers were spun from a CA+ Polyvinylpyrrolidone (PVP)/N-methyl-2-pyrrolidone (NMP)/H2O dope solution and regenerated by deacetylation. The complete deacetylation time of 0.5 h was found at a high concentration (0.2 M) NaOH ethanol (96%) solution. The reaction rate of deacetylation with 0.5 M NaOH was faster in a 50% ethanol compared to a 96 vol.% ethanol. The hydrogen bond between CA and tertiary amide group of PVP was confirmed. The deacetylation parameters of NaOH concentration, reaction time, swelling time, and solution were investigated by orthogonal experimental design (OED) method. The degree of cross-linking, the residual acetyl content, and the PVP content in the deacetylated membranes were determined by FTIR analysis. The conjoint analysis in the Statistical Product and Service Solutions (SPSS) software was used to analyze the OED results, and the importance of the deacetylation parameters was sorted as Solution > Swelling time > Reaction time > Concentration. The optimal deacetylation condition of 96 vol.% ethanol solution, swelling time 24 h, the concentration of NaOH (0.075 M), and the reaction time (2 h) were identified. The regenerated cellulose hollow fibers under the optimal deacetylation condition can be further used as precursors for preparation of hollow fiber carbon membranes.